2010
DOI: 10.1111/j.1863-2378.2009.01247.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Epidemiology of Sporadic Human Cryptosporidiosis in Scotland

Abstract: The spatial and temporal epidemiology of human cryptosporidiosis was described by analysing sporadic cases reported in Scotland from 2005 to 2007. Measures of livestock density and human population density were explored as indicators of the geographical variation in prevalence. Cryptosporidium parvum was more common in areas with lower human population densities, with a higher ratio of the number of farms to human inhabitants and with a higher ratio of the number of private water supplies to human inhabitants.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 18 publications
3
37
0
Order By: Relevance
“…A previous study with a larger sample size in the same geographical area also revealed the predominance of C. hominis with 63.9% positive specimens, although C. parvum was identified in 31.5% individuals, and was significantly more frequent in children from rural areas (Llorente et al, 2007). A similar conclusion was reported in the United States, Ireland or Scotland, where C. parvum predominates in rural areas and areas with high ruminant livestock density, whereas C. hominis is more common in the more densely human populated areas (Feltus et al, 2006;Zintl et al, 2009;Pollock et al, 2010).…”
Section: Discussionsupporting
confidence: 78%
“…A previous study with a larger sample size in the same geographical area also revealed the predominance of C. hominis with 63.9% positive specimens, although C. parvum was identified in 31.5% individuals, and was significantly more frequent in children from rural areas (Llorente et al, 2007). A similar conclusion was reported in the United States, Ireland or Scotland, where C. parvum predominates in rural areas and areas with high ruminant livestock density, whereas C. hominis is more common in the more densely human populated areas (Feltus et al, 2006;Zintl et al, 2009;Pollock et al, 2010).…”
Section: Discussionsupporting
confidence: 78%
“…It is ranked sixth of the most commonly distributed Cryptosporidium species in humans and has been reported in at least 25 sporadic cases of cryptosporidiosis. All, but one, of the cases were reported in industrialized nations (Wang et al 2008a;Davies et al 2009;Pollock et al 2009). It is also one of the most common Cryptosporidium species found in drinking source water in USA and Canada (Jiang et al 2005;Ruecker et al 2007;Karanis et al 2007;Yang et al 2008;Jellison et al 2009).…”
Section: Discussionmentioning
confidence: 94%
“…, 2004). In an environmental analysis in Scotland, increasing density or ratio of farms per person, private water supply and sheep density were all significantly associated with increasing numbers of C. parvum reports (Pollock et al. 2009).…”
Section: The Risk Of Zoonotic Transmission To Humans In Outbreaks Andmentioning
confidence: 99%